Workshop Report Promoting Risk management solutions in fragile settings of Northern Nigeria - Ajeigbe, Hakeem A.; Banerjee, Rupsha R.; Shikuku, Kelvin Mashisia; Whitbread, Anthony M. (International Livestock Research Institute, 2025)
The livestock sector in Northern Nigeria plays a crucial role in the country’s economy, contributing significantly to food security, livelihoods, and cultural identity. However, this sector faces numerous challenges, particularly in fragile settings characterized by conflict, climate variability, and socio-economic instability. Recognizing the urgent need for effective risk management solutions, the International Livestock Research Institute (ILRI) organized an interactive session aimed at promoting strategies to enhance resilience within livestock production systems. This report synthesizes insights gained during the session, focusing on key research questions that guided discussions: 1. What are the risk types prioritized in the livestock value chain? 2. How do these risks interact to compound impacts for different social groups? 3. What are the various risk management strategies currently in place? 4. What entry points exist to enhance the effectiveness of these strategies for building resilience? The report is structured to address these questions systematically, providing a comprehensive overview of the identified risks, their implications, and potential management strategies. This report highlights the significant challenges and opportunities within Nigeria's livestock sector, which is crucial to the country's agricultural economy. Northern Nigeria faces severe vulnerabilities due to climate change, including increased temperatures, variable rainfall, desertification, and extreme weather events such as floods and droughts. These factors exacerbate natural resource degradation and conflicts in pastoral areas, making them increasingly fragile.